Identification of microbes from textile dye wastewater and its antibiotic resistance from local textile factory. Issue 1 (2nd January 2023) - Mohamad Hanapi, Nur Hanis; Monajemi, Hadieh; Ismail, Azimah; Suhaili, Zarizal; Juahir, Hafizan
Abstract: This study is to identify local isolates from textile dye wastewater and its antibiotic resistance effects on the environment. The textile dye wastewater was collected from local factories and microbes were extracted from wastewater and grown on the bacterial agar. Both biochemical tests and molecular studies were performed where Gram staining, DNA extraction, PCR and Gel electrophoresis were conducted for the bacterial identification. Gram staining tests indicated the characteristics of Gram-positive bacteria. Three microbial isolates were identified as Bacillus species, Bacillus aerius (1312 bp) and Bacillus cereus (1492 bp and 1355 bp). Antibiotic resistance test was performed to observe the antibiotic resistance of these microbes. Six antibiotics were used, i.e., streptomycin, penicillin G., rifampicin, tetracycline, chloramphenicol and gentamicin. From the results, it was concluded that the local isolates were sensitive to the antibiotics introduced in the culture, indicating that they are harmless to humans and the environment.